Analisis Variabel Kegagalan Konsultan Pada Proses Pengadaan Penyedia Jasa Konsultansi Di Dinas Perumahan Pemukiman Dan Cipta Karya Kota Pekanbaru - Salman Muhamad Zulwi; Rian Trikomara; Sri Djuniati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
High levels of competition in the procurement process consulting services require consultants doing things or ways brilliant in order to obtain a positive result to win the auction. Competition to win the auction occurs in each of the consultants who will eventually obtained the consultant selected as a winner. On the other hand there are many consultants who follow the auction defeat, This event is certainly detrimental to the consultant because it has a lot of energy and money he has to spend. This study aims to determine the variables that influence the failure of the process of procurement of consulting services provider on government projects especially at Department Of Housing, Building Planning And Urban Development Pekanbaru. The research data obtained from questionnaires distributed to counterparties consultant and confirmed with the interview of the ULP Department Of Housing, Building Planning And Urban Development Pekanbaru. Data processing was done manually using Microsoft Excel and presented in a bar chart. Based on the research results, the most dominant variable failure of the procurement process consulting services provider during 2012 to 2014 is the issue of completing the legality either the legality of the company or the legality of experts, experts are not eligible and the offer price to compete.  Keywords: consulting services, questionnaire, experts, intervie